The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adsc.202001367
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effect‐Guided Rational Design of Candida antarctica Lipase B for Kinetic Resolution Towards Diarylmethanols

Abstract: Herein, we developed an electronic effect-guided rational design strategy to enhance the enantioselectivity of Candida antarctica lipase B (CALB) mutants towards bulky pyridyl(phenyl) methanols. Compared to W104A mutant previously reported with reversed S-stereoselectivity toward sec-alcohols, three mutants (W104C, W104S and W104T) displayed significant improvement of Senantioselectivity in the kinetic resolution (KR) of various phenyl pyridyl methyl acetates due to the increased electronic effects between pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…The engineering of catalytic‐tetrad residues can increase the enzyme catalytic efficiency (as shown in this study) and reconstruct the active sites for new enzymatic functions in Candida antarctica lipase B (Branneby et al, 2003; Li et al, 2021), halohydrin dehalogenase (Fox et al, 2007), and squalene‐hopene cyclase (Hammer et al, 2015). Together, these suggested that engineering the catalytic tetrad is an alternative strategy to tune enzymatic properties.…”
Section: Discussionmentioning
confidence: 84%
“…The engineering of catalytic‐tetrad residues can increase the enzyme catalytic efficiency (as shown in this study) and reconstruct the active sites for new enzymatic functions in Candida antarctica lipase B (Branneby et al, 2003; Li et al, 2021), halohydrin dehalogenase (Fox et al, 2007), and squalene‐hopene cyclase (Hammer et al, 2015). Together, these suggested that engineering the catalytic tetrad is an alternative strategy to tune enzymatic properties.…”
Section: Discussionmentioning
confidence: 84%
“…[18] Additionally, the ketone functional group could be efficiently reduced into a methylene or hydroxyl group as demonstrated by examples 5 e and 5 f in 90% and 81% yield, respectively. [19] In conclusion, we have developed a rutheniumcatalyzed direct CÀ H acyloxylation of 2-aroyl pyridines with readily accessible sodium carboxylates under mild conditions. A wide range of aliphatic and aromatic sodium carboxylate coupling partners are well suited substrates in this ruthenium-catalyzed system, offering a variety of substituted acyloxylated 2-aroyl pyridines in 45%-84% yields.…”
Section: Resultsmentioning
confidence: 96%
“…Among a variety of additives that were examined (AgBF 4 , AgNTf, KSbF 6 , KPF 6 , NaPF 6 ), AgSbF 6 proved to be superior. Notably, the desired oxygenation reaction did not occur when [RuCl 2 (p-cymene)] 2 was used as the catalyst in the absence of an additive, which can be rationalized by the in situ generation of a cationic ruthenium(II) catalyst (entries [17][18][19][20][21][22]. The yield increased to 60% upon the addition of 40 mol% AgSbF 6 as an additive (entry 23).…”
Section: Resultsmentioning
confidence: 99%
“…Three polar amino acids including Cys, Ser and Thr with similar size as alanine were introduced at the 104 position to reconstruct the substrate binding pocket with increased polarity, thereby increasing the interactions between polar side chains of residues at 104 and N atom of pyridine-4-yl in the substrate. As a result, the mutants W104C and W104T improved the S -enantioselectivity from 91% to 99% and 98%, respectively, with the similar yield compared to the mutant W104A ( Li et al, 2021 ). Similarly, the substrate binding was rationally modified by simultaneously tuning electronic interactions and steric effects, leading to up to 22-fold enhancement in the enantioselectivity of an esterase BioH towards methyl ( S )-o-chloromandelate ( S -CMM) ( Gu et al, 2015 ).…”
Section: Rational Design Strategy Based On Remodeling Interaction Net...mentioning
confidence: 93%
“…The molecular dynamics simulations showed that, as expected, the mutant V328N formed a stable hydrogen bond with the ester group of the LAC, which was exactly placed at the opposite side in the catalytic pocket compared to Ser264 in the S -selective variant ( Calvó-Tusell et al, 2022 ). Strengthening electronic interactions between substrate and enzyme active site was also used to improve the enantioselectivity of Candida antarctica lipase B (CALB) ( Li et al, 2021 ). It was difficult for CALB to catalyze the hydrolytic kinetic resolution (KR) of bulky racemic phenyl(pyridin-4-yl) methyl acetate due to the steric effect of Trp104.…”
Section: Rational Design Strategy Based On Remodeling Interaction Net...mentioning
confidence: 99%